Modeling of supercritical carbon dioxide extraction of andrographolide from Andrographis paniculata leaves by employing integral desorption concept - Kumoro, Andri Cahyo; Hasan, M. (2006)
Mathematical formulation is necessary for the optimization ans scale-up of a separation unit such as the extraction of biomolecules from their natural resources. The objective of this work is to obtain a quantitative description of the supercritical carbon dioxide extraction (SCDE) of andrographolode from Andrographis paniculata leaves. This work presents the development of a mathematical model based on first order desorption rate of solute into supercritical fluid to describe the SCDE of andrographolode from Andrographis paniculata leaves. Numerical calculation was carried out using a commercial algebraic optimization code, namely the MATLAB software. In this work, calculation was accomplished to obtain the adjustable parameter of the model using experimental data obtained from the SCDE of andrographolide at different operating temperature and pressure. The calculation results show that this model agrees very well with experimental data. Therefore, this model is capable for the modeling of SCDE of andrographolode from Andrographis paniculata leaves.